Peranan Forum Alumni Rohis 26 Terhadap Dakwah SMAN 26 Jakarta - Abdul Muiz Sa'adih; Khalid Mushthafainal Akhyar (STID DI AL-HIKMAH, 2017)
This study aims to determine the role of Alumni Forum Rohis 26 on the development of propaganda in SMAN 26, know the factors that made propaganda supporting the alumni forum Rohis 26, as well as to determine the factors inhibiting propaganda carried the alumni forum Rohis 26. This research method using approaches qualitative descriptive. Menununjukkan research results that Rohis Alumni Forum 26 has a role as one of the organizers of propaganda school, assisting the teacher control Rohis activities, both at school and outside of school, help improve students' knowledge and scientific capacity through its programs.